2011
DOI: 10.1021/ac2010185
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Coating Procedure for a High-Throughput 96-Blade Solid Phase Microextraction System Coupled with LC–MS/MS for Analysis of Complex Samples

Abstract: Biocompatible C18-polyacrylonitrile (PAN) coating was used as the extraction phase for an automated 96-blade solid phase microextraction (SPME) system with thin-film geometry. Three different methods of coating preparation (dipping, brush painting, and spraying) were evaluated; the spraying method was optimum in terms of its stability and reusability. The high-throughput sample preparation was achieved by using a robotic autosampler that enabled simultaneous preparation of 96 samples in 96-well-plate format. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
105
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 53 publications
1
105
0
Order By: Relevance
“…All coatings were prepared with approximately the same thickness (120µm). Both the coating preparation procedure, as well as information pertaining to the 96-blade SPME system, have been reported in previous works [20,21,22]. In the current study, the new coatings were prepared by mixing various particles with different weight ratios (PS-DVB-WAX:HLB 50:50 [w/w], PS-DVB-WAX:HLB 80:20 [w/w], PS-DVB-WAX:Si-IL 80:20 [w/w]) to determine the interaction effect of multi-particle coatings on metabolome coverage.…”
Section: Coating Preparationmentioning
confidence: 99%
“…All coatings were prepared with approximately the same thickness (120µm). Both the coating preparation procedure, as well as information pertaining to the 96-blade SPME system, have been reported in previous works [20,21,22]. In the current study, the new coatings were prepared by mixing various particles with different weight ratios (PS-DVB-WAX:HLB 50:50 [w/w], PS-DVB-WAX:HLB 80:20 [w/w], PS-DVB-WAX:Si-IL 80:20 [w/w]) to determine the interaction effect of multi-particle coatings on metabolome coverage.…”
Section: Coating Preparationmentioning
confidence: 99%
“…Recently, a newly developed geometry of SPME, 96-blade thinfilm microextraction (TFME), was applied in various applications [4][5][6][7]. For this configuration, the extraction phase is coated onto a blade-shaped substrate, instead of the traditional rod-shaped substrate, providing the high surface area-to-volume ratio necessary to increase the extraction phase volume, consequently enhancing extraction efficiency [2].…”
Section: Introductionmentioning
confidence: 99%
“…For this configuration, the extraction phase is coated onto a blade-shaped substrate, instead of the traditional rod-shaped substrate, providing the high surface area-to-volume ratio necessary to increase the extraction phase volume, consequently enhancing extraction efficiency [2]. Additionally, a high sample throughput is achievable with this technique with the use of a robotic autosampler that enables the simultaneous preparation of 96 samples in the 96-well-plate format [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These approaches are dipping the ber into the solution of active phase, spraying, brushing and electrospinning of the solution/slurry onto ber. 13 Among these coating methods, electrospinning has the ability to fabricate micro/nanobers, to control morphology and for orientation of nanobrous mat. [14][15][16] The applicability of electrospun bers as SPME sorbent for the extraction of both nonpolar and polar compounds was reported by Zewe et al 17 and it was found that the electrospun polymeric negative photoresist, SU-8 2100, ber coated wires displayed the best performance with low detection limits and large linear ranges for phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%